Prevalence and Predictors of Service Utilization Among Racially and Ethnically Diverse Adolescents in Foster Care Diagnosed With Mental Health and Substance Abuse Disorders - GARCIA, ANTONIO (2011)
This study examined the prevalence of mental health and substance abuse disorders and service utilization among a racially and ethnically diverse group of foster youth. Self-report data on symptoms and service receipt were used to identify whether groups of adolescents defined by their race and ethnicity were equally likely to receive services given the presence of a mental health or substance use disorder. Study findings showed that Caucasians are more likely to receive mental health services than African Americans. Race was not a significant predictor of accessing substance abuse services. Hispanic ethnicity was not a predictor of receipt of mental health or substance abuse treatment services. Implications for future research, practice, and policy are discussed.